Fighting Predatory Journals: A Strategic Solution for the Quality and Sustainability of Scientific Publications in Indonesia - Purnama, Adhy; Riyanto, Setyo; Siswanti, Indra; Nawangsari, Lenny Christina (Baca Dulu Publisher, 2024)
The phenomenon of predatory journals seriously threatens the academic ecosystem, especially in Indonesia, where the pressure to